Pelatihan Pemanfaatan Museum Sebagai Sumber Belajar Sejarah di SMA Kota Palu Provinsi Sulawesi Tengah [Training on Utilizing Museums as Learning Resources for History in Senior High Schools in Palu City, Central Sulawesi Province] - Misnah, Misnah; Nadjamuddin, Lukman; Hasan, Hasan; Iskandar, Iskandar; Rore, Idrus; Bauratu, Bauratu (UKInstitute, 2025)
Abstract. This community service activity was conducted in the form of a training titled “Museum as a Source of History Learning,” held at SMA Negeri 3 Kota Palu. The training aimed to enhance the understanding and awareness of teachers and students regarding the important role of museums as dynamic, interactive, and contextual sources for learning history. The program emphasized empowering teachers to utilize museums effectively as educational media and encouraged innovative teaching approaches aligned with advances in science and technology. The training content covered the function of museums as spaces for preserving historical and cultural heritage. Additionally, participants were introduced to specialized material on the biodiversity of Central Sulawesi, with a focus on endemic fauna from Lore Lindu National Park, such as anoa, babirusa, tarsier, and maleo birds. This broadened the students' perspectives beyond human history to include natural history and the significance of environmental conservation. The training was implemented in four stages: preparation, activities, execution, and evaluation, which included pre-tests, post-tests, and reflection to assess the effectiveness of the program and improve future learning processes. This initiative is expected to contribute significantly to improving the quality of history education while supporting cultural and environmental preservation in Central Sulawesi. Abstrak. Kegiatan pengabdian masyarakat ini dilakukan dalam bentuk pelatihan yang berjudul “Museum sebagai Sumber Pembelajaran Sejarah,” yang diselenggarakan di SMA Negeri 3 Kota Palu. Pelatihan ini bertujuan untuk meningkatkan pemahaman dan kesadaran guru serta siswa mengenai peran penting museum sebagai sumber pembelajaran sejarah yang dinamis, interaktif, dan kontekstual. Program ini menekankan pemberdayaan guru untuk memanfaatkan museum secara efektif sebagai media pendidikan dan mendorong pendekatan pengajaran yang inovatif sesuai dengan perkembangan ilmu pengetahuan dan teknologi. Materi pelatihan mencakup fungsi museum sebagai ruang untuk melestarikan warisan sejarah dan budaya. Selain itu, peserta diperkenalkan dengan materi khusus tentang keanekaragaman hayati Sulawesi Tengah, dengan fokus pada fauna endemik dari Taman Nasional Lore Lindu, seperti anoa, babirusa, tarsius, dan burung maleo. Hal ini memperluas perspektif siswa tidak hanya pada sejarah manusia tetapi juga sejarah alam dan pentingnya pelestarian lingkungan. Pelatihan dilaksanakan dalam empat tahap: persiapan, kegiatan, pelaksanaan, dan evaluasi, yang mencakup pre-test, post-test, dan refleksi untuk menilai efektivitas program serta meningkatkan proses pembelajaran di masa depan. Inisiatif ini diharapkan dapat memberikan kontribusi yang signifikan untuk meningkatkan kualitas pendidikan sejarah sekaligus mendukung pelestarian budaya dan lingkungan di Sulawesi Tengah.